Multiparameter Evaluation of the Heterogeneity of Circulating Tumor Cells Using Integrated RNA In Situ Hybridization and Immunocytochemical Analysis - Wu, Yongqi; Park, Kyoung-Joo Jenny; Deighan, Clayton; Amaya, Peter; Miller, Brandon; Pan, Quintin; Zborowski, Maciej; Lustberg, Maryam; Chalmers, Jeffery (Frontiers in Oncology, 2016)
Circulating tumor cells (CTCs) are routinely identified as cytokeratin (CK)-positive, epithelial cell adhesion molecule (EpCAM)-positive, and CD45-negative and are enriched based on EpCAM. However, there are a number of methodological challenges regarding both isolation and characterization of these rare CTCs including downregulation or absence of EpCAM in a variety of solid tumors leading to the omission of subpopulations of CTCs, difficulties in analyzing RNA and protein targets in CTCs due to the rarity of these cells, and low levels of targets and technological limitations of visualizing the targets of interest on each individual cell. Building on our previous CTC research on CD45-based negative magnetic separation and four-color fluorescent immunocytochemical (ICC) staining, RNA in situ hybridization (ISH) was applied to fluorescently target mRNA sequences corresponding to tumor-related genes at the single CTC level. Multiple categories of markers are targeted including CK, human epidermal growth factor receptor family markers, Hedgehog pathway markers, human papillomavirus markers, and protein arginine methyltransferase 5. In addition, an integrated method of RNA ISH and fluorescent ICC staining was developed to visualize CTCs on both mRNA and protein levels. The robustness of the integrated co-ICC and RNA ISH staining was demonstrated by a series of tests on representative tumor markers of different categories. The integrated staining can incorporate the advantages of both RNA ISH and fluorescent ICC staining and provide more intense signals and more specific bindings. With this integrated staining methodology, distinct staining patterns were applied in this report to facilitate the searching and characterization of rare subgroups of CTCs. These results support the existence of diverse groups of CTCs at both protein and mRNA transcript levels and provide an analytical tool for the research on CTCs of rare subgroups.